Pengaruh Penggunaan Pupuk Organik Terhadap Kulitas Tanah Pada Tanaman Kelapa Sawit (Elais Guineensis.) - Dede Setia Putra Gea (Jurnal Ilmu Pertanian dan Perikanan, 2026)
This study aims to directly observe the effect of organic fertilizer use on soil quality in oil palm plants. The method used is field observation during one plant growth cycle, by recording changes in soil characteristics in land given organic fertilizer and land without treatment. The parameters observed include soil color and texture, moisture, the presence of soil organisms, and signs of natural fertility. The results of the observation showed that soil given organic fertilizer experienced a gradual increase in quality, marked by a looser texture, darker soil color, and increased microorganism activity. This study concludes that the use of organic fertilizer has a positive impact on soil quality, which ultimately supports the growth of oil palm plants naturally and sustainably.